Newton's method for fully parameterized generalized equations. (2nd November 2018) - Ouyang, Wei; Zhang, Binbin
ABSTRACT: In this paper, our efforts are dedicated to study the application of Newton's method to a fully parameterized generalized equation in which both single-valued and set-valued functions depend on the parameter. We established results concerning parametric properties of the associated sequences of Newton's iterates, which follows the general format of the implicit function theorem paradigm.